A Problem Waits: Is it True that Resource-Based Theory (RBT) is an Empty Tautology? - Indri Dwi Apriliyanti (Policy & Governance Review, 2022)
Resource-based theory (RBT) has gained its maturity as a theory, and it has heavily shaped the path of research in the organization and management field. However, RBT has been criticized due to its quality and deemed to be a theory that is tautological. This study explores the evolution of resource-based theory (RBT) using the Thomas Kuhn cycle. Employing a critical literature review approach, this study identifies all articles related to RBT in the organization and management field from 1959 to 2021 and finds 141 articles. The findings have demonstrated that RBT has evolved, and it has become a better ‘puzzle solver’ as it provides a more comprehensive theoretical lens to analyze broader phenomenon of organization, particularly concerning its competitive advantage. Nonetheless, the study also sheds some light on the potential weaknesses of RBT. Inclusiveness of RBT is suggested to be a sign of tautology as the theory has a very broad definition of resources hence can embrace all phenomena in the field of organization’s strategic management. In addition to that, scholars find difficulty to define or operationalize several key concepts in RBT leading to obstruction in its ability to be tested empirically. And the vagueness of concepts creates a tautology problem in RBT that the theory cannot be verified or falsified. Thomas Kuhn suggests that theories can be developed, thus, despite its current weakness, RBT can still be improved by increasing accuracy of its key concepts. From the analysis, this study develops a theoretical recommendation regarding the use of RBT theory particularly in public administration research.